Does Unemployment Hysteresis Equal Employment Hysteresis? - Magnus Gustavsson; Pär Österholm (Uppsala University, Department of Economics, 2006)
This paper investigates if conclusions regarding labour market hysteresis differ depending on whether employment or unemployment rates are studied. Applying a range of unit-root tests to monthly data from Australia, Austria, Canada, Finland, Sweden, the U.K. and the U.S., we find results for employment rates that contrast those based on unemployment rates. In particular, rather than the mixed evidence for hysteresis found using unemployment rates, employment rates result in unequivocal evidence of hysteresis in Australia, Canada and the U.S.. These findings cast doubt on previous conclusions in the literature.
urn:nbn:se:uu:diva-210885
Keywords: C22; E24; J21; 330; Labour market; Persistence; Unit root test; Arbeitsmarkttheorie; Beschäftigung; Arbeitslosigkeit; Hysteresis; Unit Root Test; OECD-Staaten